Teks ucapan International Nurses Day Forum 2024 / Amir Heberd Abdullah - Abdullah, Amir Heberd (2024)
Good morning to all of you. 1. Alhamdulillah, let us extend our sincere gratitude to Allah S.W.T for giving us the opportunity to be here today for the International Nurses Day Forum 2024. I would like to thank the organizing committee for inviting me to officiate at this important event. I would also like to take this opportunity to extend a very warm welcome to all our guests from Institut Pergigian Perubatan Termaju (IPPT) and Kepala Batas Hospital. I am sure that at this congress there will be ample opportunities for the exchange of knowledge and experiences, development of networking for future collaboration, and discussion on improving nursing practice.